Baltic State Migration System: The Case of Latvian Immigrants in Sweden - Apsite, Elina; Lundholm, Emma; Stjernström, Olof (Journal of Northern Studies, 2012)
The article focuses on the migration from the Baltic States to Sweden, with a particular focus on Latvia. Two historical turns in the Baltic States’ recent history have contributed to an out-migration from the region—the restoration of independence in the early 1990s and accession to the European Union (EU) in 2004. Although these events were considered positive as they meant “open” borders for Baltic State citizens, lately the out-migration from Latvia has increased. Likewise, the global economic crisis that started in 2008 and the consequential unemployment draw attention to emerging patterns and the composition of emigrants to several destinations, but in this case particularly to Sweden. After the EU expansion Sweden did not receive as many Eastern European migrants as was expected at the time, but recent trends reveal that there has been a steady increase in the migration flow since then. The Nordic countries as a potential destination initially lacked pioneer migrants to establish social support networks that would attract newcomers, but this is now changing; statistics for 2010 show that the number of Baltic State immigrants in Sweden has grown significantly since 2008. With the economic recession and unemployment in Latvia in 2009, 2010 had even higher emigration activity than in 2004 just after the country’s accession to the EU. Nordic countries emerge as welcoming destinations to recent migrants, who state that the proximity to their home country and the labour market opportunities are the main attraction but also that a positive view of Sweden and the Swedes plays a part. Contemporary trends of migration from the Baltic States and especially Latvia under conditions of economic downturn lead to emerging pattern of migration systems between Latvia and Sweden, combining a mixture of motives and diversity of the people involved in migration chains.